2016
DOI: 10.1063/1.4947551
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Three-fold covariance imaging of laser-induced Coulomb explosions

Abstract: We apply a three-fold covariance imaging method to analyse previously acquired data [C. S. Slater et al., Phys. Rev. A 89, 011401(R) (2014)] on the femtosecond laser-induced Coulomb explosion of spatially pre-aligned 3,5-dibromo-3',5'-difluoro-4'-cyanobiphenyl molecules. The data were acquired using the "Pixel Imaging Mass Spectrometry" camera. We show how three-fold covariance imaging of ionic photofragment recoil trajectories can be used to provide new information about the parent ion's molecular structure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…By recording all fragment momenta in one experiment, data can be collected under coincidence or covariance conditions to identify meaningful correlations between different ions. 14,[48][49][50][51] The flash of light resulting from a single ion hit is generally registered in multiple pixels of the PImMS2 sensor and across multiple sequential time bins. The images presented here were consequently centroided in order to improve the momentum resolution of the data.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…By recording all fragment momenta in one experiment, data can be collected under coincidence or covariance conditions to identify meaningful correlations between different ions. 14,[48][49][50][51] The flash of light resulting from a single ion hit is generally registered in multiple pixels of the PImMS2 sensor and across multiple sequential time bins. The images presented here were consequently centroided in order to improve the momentum resolution of the data.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…, where and are number of ions measured at th laser shot. Covariance mapping has been successfully applied to treatment of few-atomic molecules [20,39,40,197,200], as well as large molecules [33,43,[203][204][205] and clusters [206][207][208][209].…”
Section: Covariance Mappingmentioning
confidence: 99%
“…Recently, Slater et al have shown that covariance measurement of CEI can be utilized to visualize the structure of the specific but relatively large molecule, 3,5dibromo-3',5'-difluoro-4'-cyanobiphenyl (BP, C13Br2F2H5N), with the aid of both supersonic expansion cooling and adiabatic molecular alignment [43,203,204]. BP is first adiabatically aligned in the laboratory frame by using a nanosecond laser pulse (1064 nm, 10 ns, 20 Hz, 8×10 11 W cm −2 ) and then irradiated using an intense femtosecond laser pulse (800 nm, 30 fs, 3×10 14 W cm −2 ).…”
Section: Complex Moleculesmentioning
confidence: 99%
“…If the explosion occurs before the molecule rearranges, its original geometry can be established from the fragment momenta [6][7][8][9][10][11][12][13][14][15][16][17][18]. This has been used to determine the structures and chirality of gas-phase molecules [13,19,20].…”
Section: Introductionmentioning
confidence: 99%